Transfer of two species of Aphanes L. to the genus Alchemilla L. (Rosaceae) - Lahora Cano, Agustín (UMA Editorial, 2024)
Recientes estudios de filogenia molecular han puesto de manifiesto que la opción taxonómica menos disruptiva en la tribu Potentilleae Sweet es incluir los taxones de los géneros Aphanes L. y Lachemilla (Focke) Rydb. en el género Alchemilla L. Se realizan dos combinaciones y se rectifican unas atribuciones incorrectas.

Recent molecular phylogeny studies have shown that the least disruptive taxonomic option in the tribe PotentilleaeSweet is to include the taxa of the genera AphanesL. and Lachemilla(Focke) Rydb. in the genus AlchemillaL. Two combinations are made and incorrect attributions are rectified.
Keywords: Análisis cladístico; Plantas - Clasificación; Rosaceae; Potentilae; Alchemilla; Aphanes